The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00020-010-1789-4
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Theory of Discontinuous Functions of Self-Adjoint Operators: Essential Spectrum

Abstract: Abstract. In the smooth scattering theory framework, we consider a pair of selfadjoint operators H 0 , H and discuss the spectral projections of these operators corresponding to the interval (−∞, λ). The purpose of the paper is to study the spectral properties of the difference D(λ) of these spectral projections. We completely describe the absolutely continuous spectrum of the operator D(λ) in terms of the eigenvalues of the scattering matrix S(λ) for the operators H 0 and H. We also prove that the singular co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…where f is a real-valued Borel function on R. It is also of interest to predict the smoothness of the mapping S → f (T + S) − f (T ) with respect to the smoothness of f . There is a vast amount of literature dedicated to these problems, see, e. g., Kreȋn, Farforovskaja, Peller, Birman, Solomyak, Pushnitski, Yafaev [4,9,16,17,24,25,[27][28][29][30], and the references therein.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where f is a real-valued Borel function on R. It is also of interest to predict the smoothness of the mapping S → f (T + S) − f (T ) with respect to the smoothness of f . There is a vast amount of literature dedicated to these problems, see, e. g., Kreȋn, Farforovskaja, Peller, Birman, Solomyak, Pushnitski, Yafaev [4,9,16,17,24,25,[27][28][29][30], and the references therein.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Pushnitski [27][28][29][30] and Yafaev [30] have been studying the spectral properties of the operator D(λ) in connection with scattering theory. If the absolutely continuous spectrum of T contains an open interval and under some smoothness assumptions, the results of Pushnitski and Yafaev are applicable, cf.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Birman and M. G. Kreȋn (see also the previous works [10], [3], and [4]): det S. / D e For discontinuous functions ' the operator A.ı/ may fail to be compact; see Section 6 in [8] and [7]. In this case the essential spectrum and the absolutely continuous spectrum of A.ı/ can be explicitly described in terms of the spectrum of the scattering matrix; see [13], [14], and [15]. This fact is closely related to the subject of this work; it gives another relationship between the spectra of '.H / '.H 0 / and S. /.…”
Section: Connection To the Birman-kreȋn Formulamentioning
confidence: 99%
“…(1) One of us (A. P.) studied the difference f (H ) − f (H 0 ) for functions f with jump discontinuities [29][30][31]. Among other things, it was shown that for the function f (λ) = 1 (−∞,a) (λ) with a > 0 the operator f (− + V ) − f (− ) is never compact, unless scattering at energy a is trivial.…”
Section: Setting Of the Problem In This Paper We Consider Functions mentioning
confidence: 99%